Eksplorasi Metode Holt’s Double Exponential Smoothing Pada Peramalan Jumlah Produksi Buah Nanas Di Provinsi Riau - Nia Khairani; Depriwana Rahmi; Annisah Kurniati; Suci Yuniati (Institut Agama Islam Negeri Fattahul Muluk Papua, 2023)
Forecasting is the systematic process of predicting what might happen in the future, based on information from the past and present, to reduce errors in estimating what will happen. Forecasting does not have to give a definite answer, but tries to approximate future reality. This research aims to forecast pineapple fruit production in Riau Province from 2023 to 2027 using Holt's Double Exponential Smoothing method. This study uses data from 2013 to 2022 obtained from the official website of the Riau Province Statistics Agency. In this study, researchers used quantitative methods. Forecasting results are measured by MAD, MSE, and MAPE metrics. The analysis results show that the forecasting accuracy rate reaches around 68.68% with the smallest forecasting error percentage of around 36.17% which is categorized as quite good forecasting. These results can help stakeholders in agriculture to manage pineapple fruit production more efficiently and accurately.